(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
The study was conducted in the 20 upazila of 10 selected major potato growing districts of Bangladesh to find out the present potato cultivation status, challenges, diversity of pests and their risks management options among the farmers. The data were collected through interview of 500 potato farmers considering 25 potato farmers from each upazila. Infections of diseases were reported to be the major problems followed by lower market price of the produced potato. Other major problems faced during potato cultivation were insect pest attack and weed attack. The BARI Alu-7 (Diamant) was most susceptible potato variety to insect pests and diseases, whereas the Lal-pakhri was the least susceptible to pests. Most of the fields (98.50%) were infested by cutworm. Among these pests, cutworm and aphid were identified as major pests and caused high and moderate infestations respectively. Others were identified as minor pests of potato with low infestations. Potato tuber worm was found as the key pest in storage condition. Rat was reported as the most infesting vertebrate storage pests. Currently cutworm and aphid were more damaging insect pest of potato in field condition than previous infestation, and potato tuber worm was more damaging insect pest in storage. Insecticide spray is the most favorable pest control method among the potato growers. Only a little portion of farmers have knowledge about integrated pest management (IPM) practices. So, it is expected the proper awareness program and planning will be taken to handle such challenges. Res. Agric., Livest. Fish.5(2): 165-174, August 2018